What are the Impacts of Food Losses on the Nutrition? - Todorova, Stela; Haralampiev, Kaloyan (Journal of Ecohumanism, 2024)
Reducing food loss and waste is enshrined in Sustainable Development Goal (SDG) 12 on Responsible Consumption and Production, and specifically in target 12.3, which seeks, by 2030, to halve per capita global food waste at the retail and consumer levels and reduce food losses along production and supply chains, including post-harvest losses. Food loss is for any food removed from the supply chain between maturity and sale, including inedible parts as these are integral to the marketed product. The main hypothesis is that the greater the loss of food, the less the supply of food per capita will be, from where the possibilities for feeding the population decrease. Based on data from the Food and Agriculture Organization (FAO), a mediation analysis will be performed with food losses as independent variables, with dependent variables measuring population nutrition and mediator variables measuring per capita food supply. Various survey methods have been applied, secondary data analysis, сimultaneous equations model(SEM), mediation analysis, as well as desktop research. The results of the study showed that the relationships between Losses Animal Products and the mediator variables are positive – greater losses lead to greater per capita supply. The relationships between per capita supply and prevalence of undernourishment are negative – larger per capita supply leads to a smaller prevalence of undernourishment.